MICROSPHERE: A PROMISING APPROACH FOR DRUG DELIVERY - Choudhury, Ananta; Deka, Debasish; Sonowal, Kashmiri; Laskar, Rahela Eyachmin (Journal of Applied Pharmaceutical Research, 2019)
The recent evolution in new drug delivery systems plays a important role in pharmaceutical industries. There are various controlled release products, Microsphere is one among all due to the sustained release and controlled release properties.Microsphere are small spherical shape characteristically free flowing powders, with diameters typically ranging from 1 ?m to 1000 ?m (1 mm). Microspheres can be produced using several natural and synthetic polymeric materials. Depending on the method, solid or porous microspheres can be obtained for specific intended applications. The variety of methods for the production of microspheres offers numerous opportunities to control the aspects of administration of the API.  It provides the prolonged therapeutic action and reduce the dosing frequency, which improve the patient compliance. To get the desired effect the drug should deliver at the target tissue in an ideal amount in the right period of time with maximum therapeutic effect and minimum side effect. Now a day?s microspheres have been used to deliver drugs, vaccines etc. The article is mainly focus on the various aspect of microspheres drug delivery system along with their method of preparation, technique to evaluate its efficiency and pharmaceutical application of microspheres.